Gender- and academic level-bias in MATS when measuring attitude towards science in Indonesia: A Rasch analysis - Ahmad Suryadi; Sahal Fawaiz; Eka Kurniati; Ahmad Swandi (Journal of Pedagogical Research, 2023)
The waning interest of students in science became a global concern. The purpose of this research was to translate, adapt, and validate the My Attitude toward Science (MATS) questionnaire instrument, which was used to measure students' attitudes toward science in the Indonesian context. We also investigated the items that contributed to gender and academic level differences in responses. To analyze the psychometric properties of the instrument, 223 students participated in the four-dimensional Indonesian variant of the MATS instrument. The unidimensionality and model fit of the four dimensions of the questionnaire were evaluated using Rasch analysis. In general, the reliability of the instruments was quite good, but the reliability of the instruments in the perception of scientists' dimensions is still relatively low (0,32). The questionnaire was incapable of distinguishing between students with positive and negative perceptions of scientists. The range of MNSQ values for all four dimensions was approximately 0.73 to 1.55. In the gender based DIF analysis, two items were identified: MATS 14 (-0.68) and MATS 21 (-0.75). In the meantime, each class responded differently to one or more items based on their academic level. In conclusion, this study concluded by recommending the simplification of the scale used to assess the perception of scientists' dimensions. It is anticipated that the Indonesian version of the MATS instrument will aid educators, researchers, and policymakers in obtaining valid and dependable data regarding student attitudes toward science. The implications and future studies on masculinity, old-scientists, and lower ATS in early high school classes have been discussed.